Radiocarbon Dating of a Speleothem Record of Paleoclimate for Angkor, Cambodia. Issue 6 (14th December 2017) - Hua, Quan; Cook, Duncan; Fohlmeister, Jens; Penny, Dan; Bishop, Paul; Buckman, Solomon
Abstract: We report the chronological construction for the top portion of a speleothem, PC1, from southern Cambodia with the aim of reconstructing a continuous high-resolution climate record covering the fluorescence and decline of the medieval Khmer kingdom and its capital at Angkor ( 9th–15th centuries AD). Earlier attempts to date PC1 by the standard U-Th method proved unsuccessful. We have therefore dated this speleothem using radiocarbon. Fifty carbonate samples along the growth axis of PC1 were collected for accelerator mass spectrometry (AMS) analysis. Chronological reconstruction for PC1 was achieved using two different approaches described by Hua et al. (2012a) and Lechleitner et al. (2016a). Excellent concordance between the two age-depth models indicates that the top 47 mm of PC1 grew during the last millennium with a growth hiatus during 1250–1650 AD, resulting from a large change in measured 14 C values at 34.4–35.2 mm depth. The timing of the growth hiatus covers the period of decades-long droughts during the 14th–16th centuries AD indicated in regional climate records.